Teaching bodies : moral formation in the Summa of Thomas Aquinas - Jordan, Mark D. (Fordham University Press, 2017)
Leading scholar of Christian thought Mark D. Jordan offers an original reading of the Summa of Theology of Thomas Aquinas. Reading backward, Jordan interprets the main parts of the Summa, starting from the conclusion, to reveal how Thomas teaches morals by directing attention to the way God teaches morals, namely through embodied scenes: the incarnation, the gospels, and the sacraments.